Composite fiberboard and preparation method thereof

By using specific raw material formulas and process steps in the preparation process of composite fiberboard, the problems of water absorption and expansion and formaldehyde release in humid environments are solved, and the effect of improving water resistance and reducing formaldehyde release is achieved.

CN119841577AInactive Publication Date: 2025-04-18JIANGSU MBOTE KITCHEN & BATH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510336157.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-21
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Existing composite fiberboards will absorb water and expand after long-term contact with humid air, and the adhesives used in the production process contain harmful substances such as formaldehyde, which affects the environment and human health.

Method used

The raw material formula including ligno fibers, composite resins, hydroxymethyl cellulose, aluminate cement, talc powder, polyvinyl alcohol, polyvinyl acetate emulsion, urea-formaldehyde resin glue and polyacrylate is used to form an emulsion liquid through process steps such as emulsification and stirring, and through vacuum air flow molding and pressurized heating and pressing, composite fiberboards with improved water resistance and reduced formaldehyde emission are prepared.

Benefits of technology

Significantly improve the water resistance and strength of composite fiberboard, reduce formaldehyde emission, and improve environmental and human health and safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention discloses a composite fiberboard and a preparation method thereof, and belongs to the technical field of artificial boards. Comprising the following raw materials in parts by weight: 34-45 parts of wood fiber, 17-26 parts of composite resin, 7-13 parts of hydroxymethyl cellulose, 5-9 parts of aluminate cement, 4-8 parts of talcum powder, 11-16 parts of polyvinyl alcohol, 9-14 parts of polyvinyl acetate emulsion, 7-11 parts of urea-formaldehyde resin adhesive, 5-9 parts of polyacrylate and 1.2-2.5 parts of a composite coupling agent. According to the composite fiberboard, the water resistance of the composite fiberboard can be improved, and the problem that harmful substances containing formaldehyde and the like are released is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a composite fiberboard and a preparation method thereof, belonging to the technical field of artificial boards. Background Art

[0002] Composite fiberboard is a board made by mixing and pressing wood fiber and synthetic resin. With the development of urbanization and the increasing awareness of environmental protection, the application prospects of composite fiberboard materials will be broader; however, after long-term contact with humid air, the current composite fiberboard will absorb moisture and swell inside the fiberboard, affecting its use; and composite fiberboard requires a large amount of adhesives in the production process, some of which contain harmful substances such as formaldehyde, with a low removal rate, affecting the environment and human health. Therefore, it is necessary to further improve the performance and quality of composite fiberboard. Summary of the invention

[0003] In order to solve at least one problem existing in the above-mentioned prior art, the present invention provides a composite fiber board and a preparation method thereof, which can not only improve the water resistance of the composite fiber board, but also solve the problem of releasing harmful substances such as formaldehyde.

[0004] In order to achieve the above-mentioned purpose, the present invention adopts the following technical scheme: a composite fiber board, comprising the following raw materials, measured by weight: 34-45 parts of wood fiber, 17-26 parts of composite resin, 7-13 parts of hydroxymethyl cellulose, 5-9 parts of aluminate cement, 4-8 parts of talc, 11-16 parts of polyvinyl alcohol, 9-14 parts of polyvinyl acetate emulsion, 7-11 parts of urea-formaldehyde resin glue, 5-9 parts of polyacrylate, and 1.2-2.5 parts of composite coupling agent.

[0005] Preferably, the composite resin consists of polyurethane resin and rosin resin.

[0006] Preferably, the composite resin is composed of polyurethane resin and rosin resin in a mass ratio of (1.5-2):1.

[0007] Preferably, the composite coupling agent consists of an aminosilane coupling agent and polymethylsilanone.

[0008] Preferably, the composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane ketone in a mass ratio of 2: (1-1.5).

[0009] Preferably, the aminosilane coupling agent is one of KH550, KH792 or KH602.

[0010] The present invention also provides a method for preparing a composite fiberboard, comprising the following steps: (1) Dissolve hydroxymethyl cellulose and polyvinyl alcohol in pure water, add composite resin, and stir and emulsify at a speed of 2000-2500 rpm to form an emulsion; (2) Adding wood fiber, aluminate cement and talcum powder to the emulsion, stirring and mixing at a speed of 300-350 rpm, then adding the composite coupling agent, stirring and mixing at a speed of 250-300 rpm, then adding polyvinyl acetate emulsion, urea-formaldehyde resin glue and polyacrylate, stirring and mixing at a speed of 100-150 rpm, to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it under pressure and heating. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank is then dried by heating in stages and then naturally cooled and dried to obtain a composite fiberboard.

[0011] Preferably, in step (1), the amount of pure water used is 6 to 8 times that of hydroxymethyl cellulose.

[0012] Preferably, in step (3), the pressing conditions are: pressure of 0.65-0.75 MPa, temperature of 75-80° C., and time of 40-50 min.

[0013] Preferably, in step (4), the drying conditions are: firstly heating to 65-70°C and maintaining for 2-2.5 hours, and then heating to 1450-1480°C and maintaining for 1-1.5 hours.

[0014] Preferably, in step (4), the drying conditions are: firstly, heating from room temperature to 65-70°C at a rate of 1-2°C / min and maintaining for 2-2.5h, and then heating to 1450-1480°C at a rate of 5-10°C / min and maintaining for 1-1.5h.

[0015] Beneficial effects of the present invention: 1) The composite fiber board of the present invention uses composite resin, polyvinyl alcohol, lignin, aluminate cement and talcum powder to improve the water resistance of the composite fiber board, prevent it from absorbing water and deforming, and significantly enhance the strength and processing performance of the composite fiber board.

[0016] 2) The composite fiberboard of the present invention also uses polyvinyl acetate emulsion, urea-formaldehyde resin glue and polyacrylate as adhesives, and cooperates with polyvinyl alcohol to effectively solve the problem of releasing harmful substances such as formaldehyde, while enhancing the internal bonding strength of the composite fiberboard and further improving the water resistance and strength of the fiberboard.

[0017] 3) The composite fiberboard of the present invention, through hydroxymethyl cellulose, polyvinyl alcohol and composite coupling agent, also promotes the combination of lignin, aluminate cement and composite resin, improves the interface bonding ability, effectively improves the water resistance of the fiberboard, and prevents it from absorbing water, deforming, expanding or even breaking in a high humidity environment. DETAILED DESCRIPTION

[0018] The following is a clear and complete description of the technical solutions in the implementation of the present invention. The described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present invention. If the specific conditions are not specified in the embodiments, they are carried out according to the normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents, instruments, and components used, they are all conventional products that can be purchased commercially.

[0019] The aminosilane coupling agent of the present invention is one of γ-aminopropyltriethoxysilane (KH550), N-(β-aminoethyl)-γ-aminopropyltrimethoxysilane (KH792) or N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (KH602).

[0020] Example 1 A composite fiberboard and a preparation method thereof, specifically as follows: (1) Dissolve 7 parts of hydroxymethyl cellulose and 11 parts of polyvinyl alcohol in 56 parts of pure water, add 17 parts of a composite resin composed of a polyurethane resin and a rosin resin in a mass ratio of 1.5:1, and stir and emulsify at a rotation speed of 2000 rpm to form an emulsion; (2) Add 34 parts of wood fiber, 5 parts of aluminate cement, and 4 parts of talc to the emulsion, stir and mix them evenly at a speed of 300m, then add 1.2 parts of a composite coupling agent composed of KH550 and polymethylsilanone in a mass ratio of 2:1, stir and mix them evenly at a speed of 250rpm, then add 9 parts of polyvinyl acetate emulsion, 7 parts of urea-formaldehyde resin glue, and 5 parts of polyacrylate, stir and mix them evenly at a speed of 150rpm to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it at a pressure of 0.65 MPa and a temperature of 75°C for 50 min. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank was then dried in stages: first, the temperature was raised from room temperature to 65°C at a rate of 1-2°C / min and maintained for 2.5 h, then the temperature was raised to 1450°C at a rate of 5-10°C / min and maintained for 1.5 h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15 mm.

[0021] Example 2 A composite fiberboard and a preparation method thereof, specifically as follows: (1) Dissolve 10 parts of hydroxymethyl cellulose and 14 parts of polyvinyl alcohol in 60 parts of pure water, add 21 parts of a composite resin composed of a polyurethane resin and a rosin resin in a mass ratio of 1.75:1, and stir and emulsify at a rotation speed of 2000 rpm to form an emulsion; (2) Add 39 parts of wood fiber, 7 parts of aluminate cement, and 6 parts of talc to the emulsion, stir and mix them evenly at a speed of 325m, then add 1.9 parts of a composite coupling agent composed of KH792 and polymethylsilanone in a mass ratio of 2:1.25, stir and mix them evenly at a speed of 275rpm, then add 12 parts of polyvinyl acetate emulsion, 9 parts of urea-formaldehyde resin glue, and 7 parts of polyacrylate, stir and mix them evenly at a speed of 125rpm to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it at a pressure of 0.7 MPa and a temperature of 78°C for 45 minutes. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank was then dried in stages: first, the temperature was raised from room temperature to 68°C at a rate of 1-2°C / min and maintained for 2.2 h, then the temperature was raised to 1465°C at a rate of 5-10°C / min and maintained for 1.2 h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15 mm.

[0022] Example 3 A composite fiberboard and a preparation method thereof, specifically as follows: (1) 13 parts of hydroxymethyl cellulose and 16 parts of polyvinyl alcohol were dissolved in 91 parts of pure water, and 26 parts of a composite resin composed of a polyurethane resin and a rosin resin in a mass ratio of 2:1 was added, and the mixture was stirred and emulsified at a rotation speed of 2000 rpm to form an emulsion; (2) Add 45 parts of wood fiber, 9 parts of aluminate cement, and 8 parts of talc to the emulsion, stir and mix them evenly at a speed of 350m, then add 2.5 parts of a composite coupling agent composed of KH602 and polymethylsilanone in a mass ratio of 2:1.5, stir and mix them evenly at a speed of 300rpm, then add 14 parts of polyvinyl acetate emulsion, 11 parts of urea-formaldehyde resin glue, and 9 parts of polyacrylate, stir and mix them evenly at a speed of 100rpm to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it at a pressure of 0.75 MPa and a temperature of 80°C for 40 minutes. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank is then dried in stages: first, the temperature is raised from room temperature to 70°C at a rate of 1-2°C / min and maintained for 2 h, then the temperature is raised to 1480°C at a rate of 5-10°C / min and maintained for 1 h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15 mm.

[0023] Example 4 A composite fiberboard and a preparation method thereof, specifically as follows: (1) Dissolve 11 parts of hydroxymethyl cellulose and 16 parts of polyvinyl alcohol in 66 parts of pure water, add 20 parts of a composite resin composed of a polyurethane resin and a rosin resin in a mass ratio of 2:1, and stir and emulsify at a speed of 2000 rpm to form an emulsion; (2) Add 40 parts of wood fiber, 7 parts of aluminate cement, and 6 parts of talc to the emulsion, stir and mix them evenly at a speed of 300 rpm, then add 2 parts of a composite coupling agent composed of KH792 and polymethylsilanone in a mass ratio of 2:1.5, stir and mix them evenly at a speed of 300 rpm, then add 11 parts of polyvinyl acetate emulsion, 10 parts of urea-formaldehyde resin glue, and 5 parts of polyacrylate, stir and mix them evenly at a speed of 120 rpm to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it at a pressure of 0.7 MPa and a temperature of 80°C for 40 minutes. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank is then dried in stages: first, the temperature is raised from room temperature to 70°C at a rate of 1-2°C / min and maintained for 2.5 h, then the temperature is raised to 1480°C at a rate of 5-10°C / min and maintained for 1.5 h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15 mm.

[0024] Example 5 A composite fiberboard and a preparation method thereof, specifically as follows: (1) Dissolve 7 parts of hydroxymethyl cellulose and 11 parts of polyvinyl alcohol in 42 parts of pure water, add 17 parts of a composite resin composed of a polyurethane resin and a rosin resin in a mass ratio of 1.75:1, and stir and emulsify at a rotation speed of 2000 rpm to form an emulsion; (2) Add 45 parts of wood fiber, 9 parts of aluminate cement, and 8 parts of talc to the emulsion, stir and mix them evenly at a speed of 300 rpm, then add 1.2 parts of a composite coupling agent composed of KH550 and polymethylsilanone in a mass ratio of 2:1.3, stir and mix them evenly at a speed of 300 rpm, then add 9 parts of polyvinyl acetate emulsion, 11 parts of urea-formaldehyde resin glue, and 5 parts of polyacrylate, stir and mix them evenly at a speed of 120 rpm to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it at a pressure of 0.65 MPa and a temperature of 80°C for 40 minutes. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank is then dried in stages: first, the temperature is raised from room temperature to 65°C at a rate of 1-2°C / min and maintained for 2.5 h, then the temperature is raised to 1480°C at a rate of 5-10°C / min and maintained for 1 h, and then naturally cooled and dried to obtain a composite fiberboard with a thickness of 15 mm.

[0025] Comparative Example 1 A composite fiberboard and a preparation method thereof are as follows: the composite resin is replaced by polyurethane resin.

[0026] Comparative Example 2 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those of Example 1, except that epoxy resin replaces polyurethane resin.

[0027] Comparative Example 3 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those of Example 1, except that: the composite resin is composed of polyurethane resin and rosin resin in a mass ratio of 1:1.

[0028] Comparative Example 4 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those in Example 1, except that KH550 replaces the composite coupling agent.

[0029] Comparative Example 5 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those of Example 1, except that polymethylsilanone is used instead of the composite coupling agent.

[0030] Comparative Example 6 A composite fiber board and a preparation method thereof are as follows: The specific details are the same as those of Example 1, except that: γ-(methacryloyloxy)propyltrimethoxysilane replaces KH550.

[0031] Comparative Example 7 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those of Example 2, except that: the composite coupling agent is composed of KH792 and polymethylsilane ketone in a mass ratio of 1:1.

[0032] Comparative Example 8 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those in Example 1, except that: the composite coupling agent is 0 parts.

[0033] Comparative Example 9 A composite fiberboard and a preparation method thereof are as follows, which are the same as Example 1, except that: the amount of polyvinyl alcohol is 0 parts.

[0034] Comparative Example 10 A composite fiberboard and a preparation method thereof, which are as follows and are the same as those in Example 1, except that: the polyacrylate is 0 parts.

[0035] Comparative Example 11 A composite fiberboard and a preparation method thereof are as follows. The specific details are the same as those in Example 1, except that: the amount of polyvinyl acetate emulsion is 0 parts.

[0036] Comparative Example 12 A composite fiberboard and a preparation method thereof, which are as follows and are the same as those in Example 1, except that: the amount of urea-formaldehyde resin glue is 0 parts.

[0037] Comparative Example 13 A composite fiber board and a preparation method thereof are as follows, which are the same as Example 1, except that: (4) the fiber board blank is then dried at high temperature: the temperature is 1500°C and maintained for 4.5 hours, and then naturally cooled and dried to obtain a composite fiber board.

[0038] Performance Testing The static bending strength and bonding strength of the composite fiber boards prepared in Example 1 to Example 5 and Comparative Example 1 to Comparative Example 11 were tested according to the method of GB / T17657-2013. The results are shown in Table 1.

[0039] The formaldehyde release of the composite fiberboards prepared in Examples 1 to 5 and Comparative Examples 1 to 11 was tested according to the method of GB / T 11718-2009 (unit: mg / cm 3 ) were tested, and the results are shown in Table 1. The water absorption and moisture deflection of the composite fiber boards prepared in Examples 1 to 5 and Comparative Examples 1 to 11 were tested according to the method in JC / T799-2007. The results are shown in Table 1.

[0040] Table 1 Performance test

[0041] It can be seen from Table 1 that the composite fiber board prepared by the raw material formula and method of Examples 1 to 5 of the present invention has excellent water resistance and significant formaldehyde removal effect; at the same time, it has excellent strength.

[0042] Through Comparative Examples 1 to 3, it is found that the composite resin of the present invention is composed of polyurethane resin and rosin resin, and the mass ratio of polyurethane resin to rosin resin is (1.5~2):1, so that the composite fiberboard has better bending resistance and impact resistance, and helps to improve water resistance.

[0043] Through Comparative Examples 4 to 8, it is found that the present invention adopts a composite coupling agent, which is composed of an amino coupling agent and methylsilicone, and the amount ratio of the amino coupling agent to the methylsilicone is 2: (1~1.5), so that the composite fiberboard has better bonding strength and mechanical properties, and the synergy of methylsilicone and the amino coupling agent can more effectively remove formaldehyde while having lower water absorption and moisture deflection, thereby improving water resistance.

[0044] Through Comparative Example 9, it is found that the present invention adopts polyvinyl alcohol to synergistically improve not only the strength of the composite fiberboard, but also helps to improve the combination of the composite resin and wood fiber, aluminate cement, and talcum powder to enhance the bonding strength; in addition, polyvinyl alcohol interacts with the composite coupling agent to further enhance the formaldehyde removal effect, while simultaneously improving the water resistance of the composite fiberboard.

[0045] Through Comparative Examples 10 and 11, it is found that the present invention uses polyacrylate, polyvinyl acetate emulsion, and urea-formaldehyde resin glue in a synergistic manner to improve the bonding strength of the composite fiberboard, which helps to improve its mechanical strength; in addition, the presence of polyvinyl acetate emulsion can react with urea-formaldehyde resin glue to greatly reduce the formaldehyde content of the adhesive.

[0046] Through comparative example 12, it is found that the staged heating adopted in the present invention is beneficial to improving the mechanical properties and adhesion of the composite fiberboard.

[0047] In summary, the present invention can not only improve the water resistance of the composite fiberboard, but also solve the problem of releasing harmful substances such as formaldehyde, and at the same time has excellent strength.

[0048] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the present invention can be implemented in other specific forms without departing from the spirit and essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

[0049] In addition, it should be understood that although the present specification is described according to implementation modes, not every implementation mode contains only one independent technical solution. This description of the specification is only for the sake of clarity. Those skilled in the art should regard the specification as a whole. The technical solutions in each embodiment may also be appropriately combined to form other implementation modes that can be understood by those skilled in the art.

Claims

1. A composite fiberboard, characterized in that: The raw materials include, by weight: 34-45 parts of wood fiber, 17-26 parts of composite resin, 7-13 parts of hydroxymethyl cellulose, 5-9 parts of aluminate cement, 4-8 parts of talc, 11-16 parts of polyvinyl alcohol, 9-14 parts of polyvinyl acetate emulsion, 7-11 parts of urea-formaldehyde resin glue, 5-9 parts of polyacrylate, and 1.2-2.5 parts of composite coupling agent; The composite resin is composed of polyurethane resin and rosin resin; The composite coupling agent consists of an aminosilane coupling agent and polymethylsilanone.

2. A composite fiberboard according to claim 1, characterized in that: The composite resin is composed of polyurethane resin and rosin resin in a mass ratio of (1.5-2):

1.

3. The composite fiberboard according to claim 1, characterized in that: The composite coupling agent is composed of an aminosilane coupling agent and polymethylsilane ketone in a mass ratio of 2: (1-1.5).

4. A composite fiberboard according to claim 1 or 3, characterized in that: The aminosilane coupling agent is one of KH550, KH792 or KH602.

5. A method for preparing the composite fiberboard according to claim 1, characterized in that: The following steps are involved: (1) Dissolve hydroxymethyl cellulose and polyvinyl alcohol in pure water, add composite resin, and stir and emulsify at a speed of 2000-2500 rpm to form an emulsion; (2) Adding wood fiber, aluminate cement and talcum powder to the emulsion, stirring and mixing at a speed of 300-350 rpm, then adding the composite coupling agent, stirring and mixing at a speed of 250-300 rpm, then adding polyvinyl acetate emulsion, urea-formaldehyde resin glue and polyacrylate, stirring and mixing at a speed of 100-150 rpm, to obtain a premix; (3) Laying the premix in a mold, forming it using vacuum airflow, and then pressing it under pressure and heating. After the pressing is completed, demolding is performed to obtain a fiberboard blank; (4) The fiberboard blank is then dried by heating in stages and then naturally cooled and dried to obtain a composite fiberboard.

6. The method for preparing a composite fiberboard according to claim 5, characterized in that: In step (3), the pressing conditions are: pressure of 0.65-0.75 MPa, temperature of 75-80°C, and time of 40-50 min.

7. The method for preparing a composite fiberboard according to claim 5, characterized in that: In step (4), the temperature is first raised to 65-70°C and maintained for 2-2.5 hours, and then raised to 1450-1480°C and maintained for 1-1.5 hours.

8. The method for preparing a composite fiberboard according to claim 5 or 7, characterized in that: In step (4), the drying conditions are: first, the temperature is raised from room temperature to 65-70°C at a rate of 1-2°C / min and maintained for 2-2.5h, and then the temperature is raised to 1450-1480°C at a rate of 5-10°C / min and maintained for 1-1.5h.

9. The method for preparing a composite fiberboard according to claim 1, characterized in that: In step (1), the amount of pure water used is 6 to 8 times that of hydroxymethyl cellulose.

Citation Information

Patent Citations

  • Production method of moisture-proof modified urea resin adhesive

    CN104762047A

  • Shaving board with low formaldehyde emission volume and preparation method of shaving board

    CN107471392A

  • High-performance composite fiberboard and preparation method thereof

    CN113072324A

  • Formaldehyde-free medium-high density fiberboard without formaldehyde addition and manufacturing method

    CN115592763A

  • Thermosetting resin composition and articles molded therefrom

    US5959038A